Effects of mountaintop removal mining and valley filling on the occupancy and abundance of stream salamanders. Issue 2 (28th December 2015) - Price, Steven J.; Muncy, Brenee' L.; Bonner, Simon J.; Drayer, Andrea N.; Barton, Christopher D.
Summary: Human‐induced land‐use changes are among the primary causes of ecosystem degradation and biodiversity loss. Across central Appalachia (USA), mountaintop removal mining and valley filling (MTR/VF) is the prevailing form of land‐use change and represents a stressor to stream ecosystems. Salamanders are the dominant vertebrate in Appalachian headwater streams. Thus, we addressed the question: Is salamander occupancy and conditional abundance reduced in streams impacted by MTR/VF? We conducted repeated counts of adult and larval salamanders within 10‐m reaches in 11 valley‐filled streams and 12 reference streams in south‐eastern Kentucky. Relationships between occupancy, conditional abundance, and site type (MTR/VF vs. reference) were modelled using the hurdle model (Ecology, 94, 2013 and 1472), where occupancy is modelled separately from abundance while accounting for differences in per‐individual detection probabilities among groups. We found mean occupancy probabilities were >0·85 for all groups in reference reaches, whereas mean occupancy probabilities were relatively lower in MTR/VF reaches (ranging from 0·23 to 0·66). Posterior means of the difference in occupancy between site types were negative across all groups, although MTR/VF stream reaches were at least 95% less likely to be occupied by spring salamander Gyrinophilus porphyriticus, adult southern two‐lined salamander Eurycea cirrigera and larval dusky salamanders Desmognathus compared to reference reaches. Posterior means of the difference in conditional abundance between MTR/VF and reference stream reaches were negative across all groups; 95% credible interval for difference in conditional abundance covered zero for only one species (red salamander Pseudotriton ruber ). After adjusting for goodness‐of‐fit, point estimates of differences in occupancy and conditional abundance still remained below zero for most species. Additionally, MTR/VF reaches had higher ion concentrations, total organic carbon and specific conductance compared to reference reaches. Synthesis and applications . Our study concludes that mountaintop removal mining and valley filling (MTR/VF) reduces salamander occupancy and conditional abundance. Although the potential mechanisms responsible for reduction are numerous, our findings suggest a change in the current regulatory framework is needed to offset the impacts of MTR/VF on stream ecosystems and biota. Reclamation techniques that enhance conditions for vegetative succession within catchments may improve habitat on reclaimed surface mines. Abstract : Our study concludes that mountaintop removal mining and valley filling (MTR/VF) reduces salamander occupancy and conditional abundance. Although the potential mechanisms responsible for reduction are numerous, our findings suggest a change in the current regulatory framework is needed to offset the impacts of MTR/VF on stream ecosystems and biota. Reclamation techniques that enhance conditions for vegetative succession within catchments may improve habitat on reclaimed surface mines.